Spatiotemporal Distribution and Damage Trends of Pseudotheraptus devastans (Dist.) on Theobroma cacao in Ghana - Godfred Kweku Awudzi; Silas Wintuma Avicor; Richard Adu-Acheampong (Psyche: A Journal of Entomology)
Pseudotheraptus devastans (Dist.), a coreid bug, feeds on pods causing extensive deformation of the pods and clumping of beans, resulting in reduced yields. This pest was considered important in the 1960s and was more prevalent on hybrid cocoa in the Eastern region of Ghana. With the increase in the use of hybrid planting materials across the entire cocoa landscape in Ghana, information on distribution and population dynamics of the pest is needed to aid effective management. The distribution survey involving 1,740 farms indicated that the pest is present in all the cocoa-growing regions. P. devastans numbers and associated damage pods were assessed monthly on 35 farms (100 trees per farm) using the visual hand-height sampling method from 2018 to 2021. The P. devastans population peaked in April, followed by a decline from June with a minor peak in August. Pest numbers and damaged pods were significantly different for the different months but not for the regions. No significant relationship was observed between P. devastans numbers sampled to hand-height and their associated damage pods. This suggests that damage can occur regardless of the quantity of pests. Regular pest monitoring in cocoa farms is needed to ensure that pest damage is spotted early enough to avoid crop loss since P. devastans numbers do not necessarily correlate with damage.